CREATION PRINCIPLES OF INTELLIGENT AUTOMATED DELIVERY MANAGEMENT SYSTEMS AT THE RAILWAY - Kyrychenko, H. I. (Science and Transport Progress, 2017)
Purpose. The paper is aimed to analyze the functioning of the existing railway informational system, as the data storage, consideration of the ways to changeover to intelligent management system, including the application of semantic approach. It is necessary to change the paradigm of automated traffic management; this determines changing the paradigm in railway operation management. The development and introduction of new Business-Intelligence-type system requires the formalized knowledge on railway transportation process to be implemented, including in the form of ontology as the model and means to formalize the knowledge. New knowledge requires using the terms and concepts to describe the new processes and management objects in railway operations. Methodology. Formalizing the knowledge one should abstract away from classical definitions such as marshaling or freight station, train station, division station, dead-end station, railway junction, railway hub etc. Unified Modeling Languages for engineering the automated systems use the definitions: the objects’ categories, the class diagrams, statechart diagrams, sequence diagrams, activity diagrams, component diagrams, link diagrams in properties etc. These concepts enable formalizing the knowledge, bringing to homogeneous representing and using them for modeling the management processes of goods delivery. Findings. The data on timing the events of goods delivery process, breakings of schedule are taken into account in set-theoretical model on scripting scenarios for goods delivery process. One of the concepts in the model on breaking of schedule (from the knowledge base of the system ASK VPUZ-E enables to take into account the influence of possible factors and the real railway operations conditions. Originality. The ways to formalize knowledge on railway transportation process as the major premise to form intelligent informational software for management system were analyzed. The set-theoretical models on goods delivery management for scripting goods delivery process’ scenarios have been developed in the paper, the examples of using the means of object-oriented modeling to construct algorithm for technological processes have been given as well. Practical value. The author suggests new terms, definitions and concepts describing the logistic business processes and enabling to changeover to formalizing the knowledge and to forming the conditions of intelligent management system of goods delivery on railways.